Methodological Rigor in Management Research Reviews - Simsek, Zeki; Fox, Brian C; Heavey, Ciaran; Liu, Shuang (Journal of management, 2025)
Review research in management, like other research traditions, demands a methodological compass to advance coherent and credible knowledge claims. Yet, the established landscape of review research lacks a common framework for guiding and assessing its methodological rigor. We conducted an exploratory scoping review, analyzing a large sample of review articles published in the Journal of Management. The review focuses on reported practices dealing with five themes embedded within all review articles: their purpose, type, design, execution, and internal alignment. By comprehensively examining manifest practices, the review reveals crucial insights into the progress and evolving methods employed in management research reviews. Synthesizing those insights with existing conceptions of rigor, we present a conceptual framework including promising research directions on the methodological rigor of review articles.